The Integrated Industrial Development of North Eastern Region Report of the Standing Committee of the Eastern Zonal Council - Planning Commission (Planning Commission, 1971)
The idea of treating the different administrative units of Assam, Nagaland, Manipur, Tripura and NEF-A as a single Zone for the purpose of industrial development in an integrated manner based on the assessed resources of the region, emanated from the Planning Minister of Assam in the- year 1964 through his letters addressed to the Prime Minister and the Deputy Chairman of the Planning Commission.
Government of India Planning Commission
Government of India Planning Commission